'A thing not beginning and not ending': using digital tools to distant-read Gertrude Stein's The Making of Americans. - Clement, Tanya E. (Literary & Linguistic Computing, 2008)
The particular reading difficulties engendered by the complicated patterns of repetition in The Making of Americans by Gertrude Stein make it almost impossible to read this text in a traditional, linear manner. However, by visualizing certain patterns and looking at the text 'from a distance' through textual analytics and visualizations, we are enabled to make readings that were formerly inhibited. Initial analysis on Making within the MONK (metadata offer new knowledge) project (http://www.monkproject.org/) has yielded evidence which suggests that the text is intricately and purposefully structured. Using text mining to retrieve repetitive patterns and treating each as a single object makes it possible to visualize and compare the three dimensions upon which these repetitions co-occurby length, frequency, and location-in a single view. Certainly, reading The Making of Americans in a traditional way appears to have yielded limited material for scholarly work, but reading the text differently, as an object of pairings or as parts of combinations, ultimately works in contrast to the supposition that the text is only meaningful to the extent that it defeats making meaning. A distant view of the text's structure allows us to read the text as an object that becomes, as it continues to turn in on itself with a centrifugal force, a whole history without beginning or ending.